Antecedents of zakat payer's trust in an emerging zakar sector - Murtala Oladimeji Abioye Mustafa, Muhammad Akhyar Adnan, Muslim Har Sani Mohamad (Emerald, 2013)

(untitled)
Purpose – The purpose of this paper is to investigate and explain the factors underlying the inclination of zakat payers to trust a particular zakat institution. Design/methodology/approach – Based on the literature review and experience survey, a context specific questionnaire was developed as the main method of quantitative data collection. The instrument was administered to a sample of Muslim professionals who observe religious seclusion in the last ten days of the Islamic fasting month (itqaf) in 12 purposely selected mosques across four states and the federal capital territory. Findings – Drawn from the resource dependence and legitimacy theories, the study finds that board capital, disclosure practices, governmental model of zakat institution, and stakeholder management were identified through the use of structural equation modeling as being the antecedents of zakat payers’ trust.